Modulation of Gonadotropin-Releasing Hormone Neuron Activity and Secretion in Mice by Non-peptide Neurotransmitters, Gasotransmitters, and Gliotransmitters - Spergel, Daniel J. (Frontiers in Endocrinology, 2019)
Gonadotropin-releasing hormone (GnRH) neuron activity and GnRH secretion are essential for fertility in mammals. Here, I review findings from mouse studies on the direct modulation of GnRH neuron activity and GnRH secretion by non-peptide neurotransmitters (GABA, glutamate, dopamine, serotonin, norepinephrine, epinephrine, histamine, ATP, adenosine, and acetylcholine), gasotransmitters (nitric oxide and carbon monoxide), and gliotransmitters (prostaglandin E2 and possibly GABA, glutamate, and ATP). These neurotransmitters, gasotransmitters, and gliotransmitters have been shown to directly modulate activity and/or GnRH secretion in GnRH neurons in vivo or ex vivo (brain slices), from postnatal through adult mice, or in embryonic or immortalized mouse GnRH neurons. However, except for GABA, nitric oxide, and prostaglandin E2, which appear to be essential for normal GnRH neuron activity, GnRH secretion, and fertility in males and/or females, the biological significance of their direct modulation of GnRH neuron activity and/or GnRH secretion in the central regulation of reproduction remains largely unknown and requires further exploration.